2020
DOI: 10.1038/s41598-020-73034-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-oxidation on the corrosion behavior of pure Ti under coexistence of solid NaCl deposit and humid oxygen at 600 °C: the diffusion of chlorine

Abstract: The effect of pre-oxidation on the corrosion behavior of pure Ti covered with a solid NaCl deposit in the humid O2 flow at 600 °C is studied. The oxide scale, formed by pre-oxidation, protects the substrate from the NaCl induced corrosion during the initial stage. However, the corrosion of the pre-oxidized sample is severely accelerated by solid NaCl after an incubation period. The chlorine, generated from the decomposition of solid NaCl, diffuses into the oxide/substrate interface as ions during the incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Inspired by the well-known fact that chloride salts ( e.g. , NaCl and KCl) could extensively corrode metals or alloys at the temperature of 400–700 °C due to the generated highly corrosive gases, we further thought that the “etching atmosphere” generated by NaCl at high temperature (Figure b) might also significantly improve the etching rate of NDs ( e.g. , etching away the adsorbed small-sized nanoparticles and rounding NDs).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Inspired by the well-known fact that chloride salts ( e.g. , NaCl and KCl) could extensively corrode metals or alloys at the temperature of 400–700 °C due to the generated highly corrosive gases, we further thought that the “etching atmosphere” generated by NaCl at high temperature (Figure b) might also significantly improve the etching rate of NDs ( e.g. , etching away the adsorbed small-sized nanoparticles and rounding NDs).…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, the oxidation of pure NDs was rather a mild process, the weight loss gradually reached 37.40% after the 5 h oxidation. The results above demonstrated that NaCl would accelerate the oxidation process of NDs under the help of the “salt-assisted etching atmosphere” generated at high temperature, leading to the etching of both diamond and nondiamond carbons, other impurities such as metals, and so forth …”
Section: Resultsmentioning
confidence: 99%
“…Although MAO specimens already have excellent corrosion resistance compared to pure Ti, micropores and defects inevitably form on their surface due to arc discharge. The micropores and microcracks can become channels for body fluid to enter the membrane and corrode the substrate ( Fan et al, 2020 ). Liang et al also confirmed that chloride ions could enter porous defects on MAO surfaces, which in turn corroded the material ( Liang et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20][21] For marine environments, many multiarea corrosion studies that include the liquid-air-interface, mud, seawater, atmosphere, and interface area have been conducted. [22][23][24] These studies have shown that corrosion occurs first at the junction of the gas and liquid phases. [25][26][27][28] It is expected that these studies will be meaningful in solving marine corrosion issues and protecting metals.…”
Section: Introductionmentioning
confidence: 99%